2012
DOI: 10.1002/ange.201205416
|View full text |Cite
|
Sign up to set email alerts
|

Anionen‐induzierte enantioselektive Cyclisierung von Diinamiden zu Pyrrolidinen durch kationische Gold‐Komplexe

Abstract: Zone Fayoum, 63514 (¾gypten) [**] Diese Arbeit wurde großzügig durch die DFG im Rahmen des Emmy-Noether-Programms gefçrdert (CZ 183/1). A.K.M. ist dankbar für ein DAAD-Promotionsstipendium. Dr. Roman Rüttinger wird gedankt für seinen experimentellen Beitrag zur Anwendung chiraler Phosphanliganden (Tabelle 1). Hintergrundinformationen zu diesem Beitrag sind im WWW unter http://dx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(3 citation statements)
references
References 114 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…[4] This low number of enantioselective transformations is mainly due to the linear coordination geometry of the ligand-Au-alkyne and the anti addition of Au and an ucleophile across an alkyne.T o address this problem, both well-defined large chiral ligands [5] and the use of chiral counter anions have been studied with some success. [6] Some of these reactions were rendered enantioselective by using other carbophilic catalysts,s uch as iridium, [7] platinum, [5c, 8] palladium, [9] and copper. [10] However, these strategies can only be applied to al imited number of transformations.A lternative approaches for highly enantioselective synthesis of complex carbo-and heterocyclicc ompounds are still in high demand.Inspired by indole alkaloids [11] (see representatives in Figure 1a), our group has developed as eries of cationic gold(I) complex-catalyzed cyclizations of alkyne-tethered indoles (e.g., 1!2,F igure 1b)t oa ccess tetracycilic scaffolds often found in akuammiline alkaloids.…”
mentioning
confidence: 99%
“…[4] This low number of enantioselective transformations is mainly due to the linear coordination geometry of the ligand-Au-alkyne and the anti addition of Au and an ucleophile across an alkyne.T o address this problem, both well-defined large chiral ligands [5] and the use of chiral counter anions have been studied with some success. [6] Some of these reactions were rendered enantioselective by using other carbophilic catalysts,s uch as iridium, [7] platinum, [5c, 8] palladium, [9] and copper. [10] However, these strategies can only be applied to al imited number of transformations.A lternative approaches for highly enantioselective synthesis of complex carbo-and heterocyclicc ompounds are still in high demand.Inspired by indole alkaloids [11] (see representatives in Figure 1a), our group has developed as eries of cationic gold(I) complex-catalyzed cyclizations of alkyne-tethered indoles (e.g., 1!2,F igure 1b)t oa ccess tetracycilic scaffolds often found in akuammiline alkaloids.…”
mentioning
confidence: 99%
“…Optimization of the reaction conditions revealed that cationic ( t‐ Bu) 3 PAu + with a bulky BINOL phosphate counterion 176 resulted in the best yields and ee s (Scheme ). The catalyst was prepared prior to addition to the reaction, as in situ formation gave inferior the results 119…”
Section: N‐nucleophilesmentioning
confidence: 99%
“…(+)‐Mesembrine, a stimulant originally isolated from the succulent plant Sceletium tortuosum , is a well known standard system to test novel stereoselective methodologies. The Czekelius group envisioned to apply their gold‐catalyzed desymmetrisation reaction for the enantioselective preparation of pyrrolidines with a quarternary stereocenter in 3‐position for the synthesis of the natural compound. While chiral ligands proved unsuccessful, a chiral counter anion strategy delivered the desired pyrrolidines in high enantioselectivities.…”
Section: Introductionmentioning
confidence: 99%